Multiplicative Stochastic Model of the Time Interval between Trades in Financial Markets - Gontis, V. (Nonlinear Analysis: Modelling and Control, 2002)
Stock price change in financial market occurs through transactions, in analogy with diffusion in stochastic physical systems. The analysis of price changes in real markets shows that long-range correlations of price fluctuations largely depend on the number of transactions. We introduce the multiplicative stochastic model of time interval between trades and analyze spectral density and correlations of the number of transactions. The model reproduces spectral properties of the real markets and explains the mechanism of power law distribution of trading activity. Our study provides an evidence that statistical properties of financial markets are enclosed in the statistics of the time interval between trades. Multiplicative stochastic diffusion may serve as a consistent model for this statistics.
Keywords: statistical analysis; financial markets; stochastic modelling